Utilization of the Public Health Ordinance to prevent nosocomial spread in a case of acute measles-associated psychosis - Chen Stein-Zamir; Nitza Abramson; Hagit Sonnenfeld-Alroey; Jacob Charnes; Dana Eckstein; Aryeh Dienstag; Dana Wolf; Allon E. Moses; Yoram G. Weiss (Israel Journal of Health Policy Research, 2021)
Abstract Measles is a highly contagious disease. A 24 years old patient, recently exposed to measles (unvaccinated), presented in the emergency department with severe agitation, compatible with an acute psychotic episode, during the measles epidemic which spread in Israel in 2018–2019. Upon hospital admission, strict isolation was instructed, yet, without compliance, probably due to the patient’s status. Measles diagnosis was promptly confirmed. As measles transmission was eminent, public health measures were employed through immediate implementation of the section 15 of the Public Health Ordinance, allowing for compulsory short-term isolation. The patient’s condition improved within a few days and the measures were no longer necessary. This measles case occurred in the pre-Coronavirus disease 2019 (COVID-19) epidemic when use of a Public Health Ordinance was considered an extreme measure. This is in contrast to the current global use of Public Health laws to enforce strict quarantine and isolation on persons infected or potentially exposed to COVID-19. Nevertheless, minimizing infectious diseases transmission is a core function of public health law. Utilizing legal enforcement in circumstances of immediate public health hazard, such as nosocomial measles transmission, necessitates careful consideration. The integrative clinical and public health approach and prompt measures employed in this exceptional case, led to prevention of further infection spread.